Need of Specialized Courses in Advance Nursing Education in Nepal - Rai, Lalita; KC, Takma; Adhikari, Raj D; Acharya, Devaka; Sharma, Muna; Gautam, Roshani; KC, Tulaza; Das, Indra K; Shrestha, Shristy (Journal of Institute of Medicine Nepal, 2023)
Introduction: Nursing specialization and certification of skill contribute nursing professionalism that improve nursing practice in an identified specific area within the entire field of professional nursing. Methods: A descriptive cross-sectional survey was used for assessing the need of specialized courses in advanced nursing. Data was collected from January to March 2022 through an online survey among 354 nurses working in Nepal. Collected data was entered into SPSS version 16 and expressed by using descriptive statistics. Results: The findings showed that more than half (54.5%) of the participants were age group of 20-29, 99.4% were females, 50.3% had bachelor’s degree, 60.7% worked in government and 70.3% had working experience less than 10 years. Almost all (98.8%) felt importance of specialized courses in higher education and the needs of advanced courses (72.9%) and especially in critical care (53.1%) Almost allrespondents (95.2 to 90.7%) perceived these courses increase self-esteem and morale, promote quality patient care, increase confidentiality and creditability, ensure competency, validate nurses’ knowledge and expertise, advancement of professional career ladder and clinical expert and increase professional accountability. Majority of them perceived (77.4%-57.6%) that specialty courses increase access to job-related power, obtain noticeable financial benefits and perform excellence services. Almost all (91.0%) of them perceived that it is beneficial to maintain professionalism. Conclusion: This study concluded that almost all graduate nurses felt specialty courses in masters degree for personal and professional development. Thus it is strongly recommended to initiate different specialized courses at the postgraduate level.